Multifunctional pMGF505-7R Is a Key Virulence-Related Factor of African Swine Fever Virus - Huang, Li; Li, Jiangnan; Zheng, Jun; Li, Dan; Weng, Changjiang (Frontiers in Microbiology, 2022)
African swine fever virus (ASFV) is the etiological agent of African swine fever (ASF), and it is an enveloped, icosahedral, double-stranded DNA virus with a genome length ranging from 170 to 193 kb. The ASFV genome contains at least five multigene families (MGFs): MGF100, MGF110, MGF300, MGF360 and MGF505 at the right and left terminal variable regions. The members of the same MGF family are most similar and have conserved sequence motifs, whereas the genetic diversity of different MGF families varies widely. MGF genes play a crucial role in determining ASFV host range, virulence and reducing early cell death post-infection. pMGF505-7R is a multifunctional protein. Recent research advances of pMGF505-7R provide a few new clues to understand the functions of pMGF505-7R either in antagonizing the induction of type I IFN production and IFN downstream signaling or in suppressing inflammatory responses by inhibition of NF-κB signaling and NLRP3 inflammasome, which may be related to ASFV infection-induced pathogenesis.